Proceedings of Latin American &Amp; Caribbean Petroleum Engineering Conference 2007
DOI: 10.2523/107926-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Generation, Migration, and Accumulation Related to Igneous Intrusions: An Atypical Petroleum System From the Neuquen Basin of Argentina

Abstract: fax 01-972-952-9435. AbstractThe stratigraphic record of the Altiplanicie del Payún area, in the Northern Platform of the Neuquén Basin, Argentina, includes Tertiary sills and laccolites that reach thicknesses of up to 600 m. Occurrence of thermally immature oil-prone shales of the Late Jurassic Vaca Muerta and the Hauterivian Agrio Formations is profusely documented in the area. However, when sills have intruded the Vaca Muerta shales, source rock sections become mature, displaying a wideranging maturity spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, bitumen mines are numerous and some of them are exceptionally large. Some authors have suggested that maturation and migration of petroleum in the northern Neuqu en Basin could be, at least in part, due to volcanic or magmatic activity (Rodriguez et al, 2007(Rodriguez et al, , 2009Witte et al, 2012). Nevertheless, there are still many questions about such a possible correlation.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, bitumen mines are numerous and some of them are exceptionally large. Some authors have suggested that maturation and migration of petroleum in the northern Neuqu en Basin could be, at least in part, due to volcanic or magmatic activity (Rodriguez et al, 2007(Rodriguez et al, , 2009Witte et al, 2012). Nevertheless, there are still many questions about such a possible correlation.…”
Section: Introductionmentioning
confidence: 96%